2013
DOI: 10.1007/s13202-013-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of cuttings transport with foam in deviated wellbores using computational fluid dynamics

Abstract: Foam is non-Newtonian pseudo-plastic fluid, which is used for drilling, well intervention, and stimulation. Predicting the cutting transport efficiency of foam in the wellbore annulus is very important to optimize the drilling process. In this paper, the cuttings transport process with foam is numerically simulated using an Eulerian twophase model in inclined wellbores. A computational fluid dynamics (CFD) software package called FLUENT was used for this goal. The effect of foam quality, foam velocity, drill p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…CFD studies using foam as the circulating fluid have shown that the power law model performs better than the Herschel-Bulkley model in predicting cuttings transport phenomena. (Rooki et al 2014;Rooki et al, 2015). The authors examined the effect of foam quality, foam velocity, drill pipe rotation and wellbore inclination on the cuttings transport efficiency and concluded that cuttings removal is enhanced by increasing foam quality and pipe rotation.…”
Section: Related Literaturementioning
confidence: 99%
“…CFD studies using foam as the circulating fluid have shown that the power law model performs better than the Herschel-Bulkley model in predicting cuttings transport phenomena. (Rooki et al 2014;Rooki et al, 2015). The authors examined the effect of foam quality, foam velocity, drill pipe rotation and wellbore inclination on the cuttings transport efficiency and concluded that cuttings removal is enhanced by increasing foam quality and pipe rotation.…”
Section: Related Literaturementioning
confidence: 99%
“…Parameters such as annular flow rate, rate of penetration, fluid density, effective fluid viscosity, cuttings size, cuttings density, well inclination and pipe/hole eccentricity play leading roles in cuttings transport performance of drilling fluid (Ozbayoglu et al 2004;Stan & Avram 2014). In the same vein, other factors such as fluid flow regime and pipe rotation have also been observed to have a great impact on drilled cuttings transport in vertical, deviated, and horizontal wellbores Ozbayoglu et al 2008;Rooki et al 2014;Tomren et al 1986). …”
Section: Introductionmentioning
confidence: 99%
“…The kinetic theory modelling for interparticle collisions, extended from the kinetic theory of gases, is applicable to dense particulate systems where the transport of the particle phase is dominated by inter-particle collisions (Fan and Zhu, 2005). However, the most common method of analysis of cuttings transport phenomena is the RANS equations implemented within the Eulerian framework (Bilgesu et al 2002;Bilgesu et al 2007;Mishra, 2007;Sorgun, 2010;Ofei et al 2014;Rooki et al 2014;Rooki et al 2015;Heydari et al 2017). These investigations majorly evaluate the impact of several drilling variables on the efficiency of cuttings transport with respect to the cuttings volume fraction.…”
Section: Figmentioning
confidence: 99%